Unveiling Local Cultural Tourism: Strategies For Development In The Digital 5.0 Era - Sujoko Winanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The convergence of digital technologies with cultural tourism has become increasingly significant in the era of Digital 5.0. This paper explores the potential strategies for developing cultural tourism based on local heritage in this digital age. The objective of this research is to analyze and propose effective strategies for the development of cultural tourism leveraging local heritage in the context of Digital 5.0. This research adopts a library research approach to gather relevant literature, scholarly articles, and case studies related to cultural tourism, local heritage, and digital technologies. The collected information is critically analyzed to identify emerging trends and effective strategies for developing cultural tourism in the Digital 5.0 era. The findings reveal several key strategies for the development of cultural tourism based on local heritage in the Digital 5.0 era. Firstly, leveraging digital platforms and social media for promoting cultural attractions and engaging with tourists. Secondly, fostering partnerships between local communities, governments, and tourism stakeholders to preserve and showcase cultural heritage. Thirdly, integrating immersive technologies such as virtual reality (VR) and augmented reality (AR) to enhance visitor experiences and storytelling. Fourthly, implementing sustainable tourism practices to ensure the preservation of cultural assets for future generations. Lastly, investing in digital skills training and capacity building among local communities to actively participate in the digital tourism ecosystem